2021
DOI: 10.1515/dmdi-2020-0164
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 and CYP3A4 variants influence the risk and outcome of COVID-19 infection among rheumatoid arthritis patients maintained on hydroxychloroquine

Abstract: Objectives Hydroxychloroquine (HCQ) has been used as an off label for the management of coronavirus disease (Covid-19) infection with other drugs. However, different genetic variants can affect the metabolism of HCQ leading to inter-individual differences in its efficacy. In this study, we investigated the effects of variants in CYP2D6, CYP3A4 and CYP3A5 on the risk of Covid-19 infection among patients receiving HCQ for controlling rheumatoid arthritis (RA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…In carriers of CYP2D6*4 (AA), HCQ is poorly metabolized which results in reduced formation of desethyl HCQ, thus probably diminishing the efficiency of HCQ in preventing COVID-19 viruses from entering cells. Lower levels of desethyl HCQ in individuals with CYP2D6*4 (AA) were found to be associated with a significantly higher grade of ground-glass opacities in the chest CT compared to wild and heterozygous carriers (but the p-value was >0.05) [15]. Due to the fact that both CQ and HCQ were found to inhibit CYP2D6 activity, they may not only potentiate the effects of other CYP2D6 substrates, including carvedilol and labetalol but also reduce the effectiveness of prodrugs that are activated by CYP2D6 (codeine and tramadol) [72,73].…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 92%
See 4 more Smart Citations
“…In carriers of CYP2D6*4 (AA), HCQ is poorly metabolized which results in reduced formation of desethyl HCQ, thus probably diminishing the efficiency of HCQ in preventing COVID-19 viruses from entering cells. Lower levels of desethyl HCQ in individuals with CYP2D6*4 (AA) were found to be associated with a significantly higher grade of ground-glass opacities in the chest CT compared to wild and heterozygous carriers (but the p-value was >0.05) [15]. Due to the fact that both CQ and HCQ were found to inhibit CYP2D6 activity, they may not only potentiate the effects of other CYP2D6 substrates, including carvedilol and labetalol but also reduce the effectiveness of prodrugs that are activated by CYP2D6 (codeine and tramadol) [72,73].…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 92%
“…The authors suggested that the occurrence of CYP polymorphisms may explain the wide variation in this drug levels in the blood. In turn, individuals with the CYP2D6*4 (rs3892097) variant have hardly any or even no CYP2D6 activity as a result of a splicing defect in an intron (between the third and fourth exon) [15,71]. Hareedy et al [15] hypothesized that desethyl HCQ could be primarily responsible for the actions of HCQ, therefore the rate of its formation via CYP2D6 and other CYP enzymes could modify COVID-19 status among HCQ receivers for rheumatoid arthritis.…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 99%
See 3 more Smart Citations